Structural Analysis of part of the Nigerian South-western Basement Complex using aeromagnetic data - John S. Kayode (Science Faculty of Chiang Mai University, 2019)
Valuable and precious subsurface minerals have been continuously mined illegally in the region of Omu-Aran area in parts of the Nigerian South-western Precambrian Basement Complex. An aeromagnetic data obtained from the Nigerian Geological Survey Agency was analysed to delineate various subsurface geological structures in this area. The subsurface characteristics enrichment of the data was carried out using Fast Fourier Transforms, and the Euler Deconvolution methods that helped in the establishment of the different subsurface magnetic anomalies basement structures emplaced in this part of the Nigerian South-western Precambrian Basement Complex. The study aimed at mapping the main rock types found in the undifferentiated schist that includes some gneiss, schist, quartzite and quartz schist and granite-gneiss in the basement rocks of the area. It also includes delineating, as well as estimating the depths to, the magnetic source of the Ore bodies. Regional- residual separation was applied to the total aeromagnetic data to produce a total magnetic intensity map with the application of Oasis Montaj (2014 software version). Depths to the shallow magnetic anomalies source rock bodies were estimated together with various structural indices that varied between about 0.5SI and 3.0SI at the greatest depth to the shallow anomaly of about 1100m, with the aim of determining the greatest depths approximation for all the subsurface geological structural features in the area.